2010
DOI: 10.1504/ijpp.2010.032305
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous determination of FDI growth and economic growth: the OECD case

Abstract: This paper tests the endogenous relationship between FDI growth and economic growth using a panel dataset for 23 OECD countries for the period 1975-2004. In particular we estimate a twoequation simultaneous equation system with the generalized methods of moments (GMM) that treats economic growth and FDI growth as endogenous variables. We find that FDI growth and economic growth are significant determinants of each other. We also find that export growth rate and human capital are statistically significant deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A study for the endogenous relationship between FDI and economic growth using panel data from 23 OECD countries for 1975-2004 concluded that FDI positively affects economic growth (Turkcan & Yetkiner, 2010). Likewise, it revealed that economic growth stimulates the growth rate of FDI inflow.…”
Section: Empirical Literaturementioning
confidence: 99%
“…A study for the endogenous relationship between FDI and economic growth using panel data from 23 OECD countries for 1975-2004 concluded that FDI positively affects economic growth (Turkcan & Yetkiner, 2010). Likewise, it revealed that economic growth stimulates the growth rate of FDI inflow.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The market-seeking FDI considers the market size and market growth of the host economy. Thus, FDI and economic growth are important determinants of each other (Turkcan, 2008).…”
Section: Framework Of Analysismentioning
confidence: 99%
“…The Link between Foreign Direct Investment and Gross Domestic Product FDI refers to the investments made by particular companies and enterprises in other countries (Kaur et al 2013;OECD 2022;Akiri and Ushie 2020;Ramasamy and Yeung 2022). FDI generally refers to the long-term investment of capital, which is central to the integration of the international economy as it ensures stable economic ties (Türkcan et al 2008;OECD 2022;Donaubauer et al 2022). FDI makes it possible for companies to transfer assets between nations while also directly controlling business activities such as production, manufacturing, and distribution (Donaubauer et al 2022).…”
Section: The Link Between Foreign Direct Investment and Gross Domesti...mentioning
confidence: 99%
“…Foreign investment falls into two broad categories: foreign direct investment (FDI) and foreign portfolio investment (FPI) (Ullah and Tahir 2022;Botta 2018;Tsaurai 2022). In many countries, foreign investment is used to collect the capital necessary for overcoming liquidity (Türkcan et al 2008;Gunaydin and Tatoglu 2005;Agyapong and Bedjabeng 2020). Foreign investment is commonly used as a catalyst for economic development (Ullah and Economies 2023, 11, 188 3 of 21 FPI in the ten countries sampled.…”
Section: Introductionmentioning
confidence: 99%